2008
DOI: 10.14429/dsj.58.1699
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Ammonium Perchlorate in thePresence of Nanosized Ferric Oxide

Abstract: The catalytic effect of two different sizes of a-Fe 2 O 3 nanoparticles synthesised using an electrochemical method was investigated on the thermal decomposition of ammonium perchlorate (AP) using differential scanning calorimetry as a function of catalyst concentration. The nanosized ferric oxide particles exhibited more of a catalytic effect on the thermal decomposition of AP than commercial Fe 2 O 3 particles. A lowering of the high-temperature decomposition of AP by 59 o C was observed after mixing with 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…This way, they permit burning rate tailoring to fit a specific grain design. Since the combustion mechanism of propellants is very much dependent upon the decomposition of ammonium perchlorate, there are many studies concerning the catalytic effect of nanosized ferric oxide on thermal decomposition of the oxidizer (Ma et al 2006;Joshi et al 2008;Fujimura and Miyake 2010).…”
Section: Thermal Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…This way, they permit burning rate tailoring to fit a specific grain design. Since the combustion mechanism of propellants is very much dependent upon the decomposition of ammonium perchlorate, there are many studies concerning the catalytic effect of nanosized ferric oxide on thermal decomposition of the oxidizer (Ma et al 2006;Joshi et al 2008;Fujimura and Miyake 2010).…”
Section: Thermal Combustionmentioning
confidence: 99%
“…In the field of solid propulsion, nanosized transition metallic oxides such as iron oxide, hematite (α-Fe 2 O 3 ) and maghemite (g-Fe 2 O 3 ) are materials that stand out as burn catalysts in thermal combustion reactions (Joshi et al 2008;Chaturvedi et al 2012;Patil et al 2006).…”
Section: Thermal Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors studied the thermal decomposition of AP/hydroxyl-terminated polybutadiene (HTPB)-based composite propellant both in the presence and absence of nanoferric oxide and achieved high heat release, up to 40% with the retention of well-separated necklace-like structure of -Fe 2 O 3 in HTPB [70]. Joshi et al [24] studied the effect of various percentages of nanosized Fe 2 O 3 as additive in AP. Results show enhanced thermal decomposition with increased percentage of additive.…”
Section: Effect Of Nanosized Oxides As Compared To Bulk Sized Oxidesmentioning
confidence: 99%
“…Recent investigations have shown that nanoparticles of transition metal oxides (TMOs), without any agglomeration can increase the burning rate [22] of propellants. The efficiency of catalytic action increases sharply in nanosized oxide particles than microscale oxide particles [23,24]. The size distribution, morphology and nanostructure of particles are very important characteristics and they do affect the kinetics of decomposition of AP.…”
Section: Introductionmentioning
confidence: 99%